5x+27=30+0.5x 100-4(8-3x)=200 3.5x-1.2=2.7x+3 7(x5x+27=30+0.5x100-4(8-3x)=2003.5x-1.2=2.7x+37(x+4)=2(2-x)+3(4x-2)19x-5(3x-4)=242(4x-3)+(15-2x)=24+12

来源:学生作业帮助网 编辑:作业帮 时间:2022/12/02 18:46:54
5x+27=30+0.5x 100-4(8-3x)=200 3.5x-1.2=2.7x+3 7(x5x+27=30+0.5x100-4(8-3x)=2003.5x-1.2=2.7x+37(x+4)=2(2-x)+3(4x-2)19x-5(3x-4)=242(4x-3)+(15-2x)=24+12

5x+27=30+0.5x 100-4(8-3x)=200 3.5x-1.2=2.7x+3 7(x5x+27=30+0.5x100-4(8-3x)=2003.5x-1.2=2.7x+37(x+4)=2(2-x)+3(4x-2)19x-5(3x-4)=242(4x-3)+(15-2x)=24+12
5x+27=30+0.5x 100-4(8-3x)=200 3.5x-1.2=2.7x+3 7(x
5x+27=30+0.5x
100-4(8-3x)=200
3.5x-1.2=2.7x+3
7(x+4)=2(2-x)+3(4x-2)
19x-5(3x-4)=24
2(4x-3)+(15-2x)=24+12

5x+27=30+0.5x 100-4(8-3x)=200 3.5x-1.2=2.7x+3 7(x5x+27=30+0.5x100-4(8-3x)=2003.5x-1.2=2.7x+37(x+4)=2(2-x)+3(4x-2)19x-5(3x-4)=242(4x-3)+(15-2x)=24+12
1,5x-0.5x=30-27
2.5x=3
x=1.2
2,100-32-12x=200
68-12x=200
12x=68-200
12x=﹣132
x=-11
3,3.5x-1.2=2.7x+3
3.5x-2.7x=3+1.2
0.8x=4.2
x=5.25
4,7x+28=4-2x+12x-6
7x+2x-12x=﹣2﹣28
9x-12x=﹣30
﹣3x=-30
x=10